Analyzing Bullying Behavior and Its Implications for Guidance and Counseling Services at MTs Muhammadiyah Curup - Imam Rifai; Hartini; Syamsul Rizal (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Bullying remains a serious concern in school environments because of its adverse effects on students’ psychological well-being, social relationships, and academic achievement. Despite existing preventive efforts, bullying continues to occur at MTs Muhammadiyah Curup, highlighting the need for a more systematic and comprehensive guidance and counseling intervention. This study aims to analyze the forms of bullying behavior, identify the factors contributing to bullying, and develop a guidance and counseling program for addressing bullying in the school context. A Research and Development (R&D) approach was employed using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. Data were collected through observations, interviews, questionnaires, and documentation and analyzed descriptively to inform program development and evaluation. The findings indicate that bullying behavior among students was categorized as very high and included physical, verbal, relational, cyber, and prejudice-based bullying. The identified contributing factors comprised individual characteristics, family environment, peer influence, school environment, and social media. The developed guidance and counseling program was implemented through classroom guidance, content mastery services, and group counseling and was found to enhance students’ understanding of bullying, communication skills, and positive social attitudes. These findings demonstrate that a structured guidance and counseling program can provide a systematic approach to addressing bullying and strengthening preventive efforts within the school environment. The study contributes a development-based intervention framework that can support school counselors and educational institutions in fostering safer, more supportive, and more conducive learning environments.